Penggunaan E-Learning Madrasah dalam Pembelajaran Daring pada Masa Pandemi Covid-19 - Nisak, Khoirun (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
Education makes a major contribution to the progress of a nation and is a vehicle for forming an intelligent society that will give the nuances of an intelligent life as well. The implementation of education for the past year has not taken place in classrooms due to the Covid-19 (Corona Virus Disease 2019) pandemic. This situation forces the government to issue policies in education, including implementing online teaching and learning. Online learning is learning on the internet using online learning applications. To improve the quality of learning Islamic Religious Education materials in madrasas, the efforts of teachers in managing online learning are very important, one of which is the Madrasah E-Learning application. Data collection techniques using observation, questionnaires, documentation, and interviews. The results showed that: (1) The use of Madrasah E-Learning in Fiqh online learning at MAN 1 Kediri there were three stages, namely the learning planning stage, the learning process, and the learning evaluation process. (2) Fiqh online learning during the Covid-19 pandemic, all teachers use the Madrasah E-Learning application which is followed by students. 89% of respondents take Fiqh online learning and in general students use the Madrasah E-Learning application even though it has several obstacles or the most important obstacle, namely an unstable internet network.